Clarification of Ageism in the Care System - Saeid Mehri; Mohammad Ali Hosseini; Masoud Fallahi-Khoshknab; Farahnaz Mohammadi Shahbelaghi; Saeed Akbari Zardkhaneh (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: The analysis of the concept of ageism will help us to achieve a similar, clear, and understandable definition of ageism in the care system. The aim of this study was clarification of the ageism in caring system. Methods & Materials: We utilized the Walker and Avant's model in this study. In a review of literature from 1969 to September 2018, sources were included on the basis of the definition, functions, properties, premises, consequences, and empirical referents of the ageism concept. Results: According to our analysis, the main attribute of the concept of ageism is that the ageism is a discriminatory process towards the elders which can have a positive or negative aspect with a conscious and unconscious manifestation in the cognitive, affective, and behavioral components in three micro, meso and macro levels and can be self-directed or other-directed. Conclusion: Since the concept of ageism in our country is relatively new and unknown, this concept analysis by clarifying the ageism, with understanding this concept in the care system, can improve implementation of more extent studies and development of research tools for identification of its barriers and facilitators and its execution.